2017
DOI: 10.1093/aob/mcx145
|View full text |Cite|
|
Sign up to set email alerts
|

On the origins and domestication of the olive: a review and perspectives

Abstract: The olive is a relevant model for improving our knowledge of domestication processes in clonally propagated perennial crops, particularly those of the Mediterranean Basin. Future studies on the ecological and genomic shifts linked to domestication in olive and its associated community will provide insight into the phenotypic and molecular bases of crop adaptation to human uses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
149
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 158 publications
(162 citation statements)
references
References 215 publications
(344 reference statements)
11
149
1
1
Order By: Relevance
“…A similar ERH was also proposed in the past for the olive tree but genetic data sampled throughout the Mediterranean support a different scenario (Besnard et al, 2017;Breton, Tersac, & Bervillé, 2006).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…A similar ERH was also proposed in the past for the olive tree but genetic data sampled throughout the Mediterranean support a different scenario (Besnard et al, 2017;Breton, Tersac, & Bervillé, 2006).…”
Section: Discussionsupporting
confidence: 78%
“…In the Pleistocene, after the onset of the Mediterranean climate, it is noteworthy that a blatant thermophilous forest community with Ceratonia and Olea was identified by 1.4 Ma pollen records at Camerota (S Italy) (Olea: 10% and Ceratonia: 12% of the pollen assemblage; Brenac, 1984). Fossil data and our phylogenetic results identified carob tree as a 'pre-Mediterranean' lineage (Herrera, 1992) and its ancestors probably were widely distributed around the Tethys Sea during the Paleogene (Palamarev, 1989) in tropical forests that were impoverished by the successive extinc- Myrtus communis L. (Besnard, Terral, & Cornille, 2017;Désamoré et al, 2011;Migliore et al, 2018); but are congruent with the low plastid variation observed in Laurus nobilis L. (Rodriguez-Sanchez, Guzmán, Valido, Vargas, & Arroyo, 2009) and even higher than in Celtis occidentalis L.…”
Section: Discussionmentioning
confidence: 55%
“…Selfing in cultivated olives could indeed result from the artificial selection of self-compatible mutants over millennia, particularly via their vegetative propagation (Manrique et al, 2019;McKey, Elias, Pujol, & Duputié, 2010;Rowlands, 1964). Recurrent admixture events between divergent olive gene pools (East vs. West;Besnard, Terral, & Cornille, 2018) may also result in a huge phenological variation in the mating system of the cultivated olive, and more frequent selfing is expected in admixed individuals (as shown for instance in hybrids of ash trees and beets; Arnaud, Fénart, Cordellier, & Cuguen, 2010;Gérard, Klein, Austerlitz, Fernández-Manjarrés, & Frascaria-Lacoste, 2006). This context could also explain contrasted results reported on the genetic determinism of self-incompatibility in Mediterranean olives (Farinelli et al, 2018;Saumitou-Laprade, Vernet, Vekemans, Castric, et al, 2017).…”
Section: On the Diallelic Self-incompatibility System (Dsi) In Olivesmentioning
confidence: 99%
“…GenBank accession number of complete plastomes and mitogenomes is indicated. For the six olive accessions, the cytoplasmic DNA lineage and haplotypes (according to Besnard et al, 2007Besnard et al, , 2018 Accessions only used for the assembly of 52 conserved mitochondrial DNA regions (Table S6). indels) and their lower sequencing depth compared to their plastid homologues (for the detailed procedure, see Van de Paer et al, 2016).…”
Section: Assembly Annotation Of Organellar Dna and Identification mentioning
confidence: 99%